La segunda vuelta electoral en los sistemas presidenciales iberoamericanos (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2013)
Most American countries elect their presidents in electoral systems that provide for a runoff between the top two candidates if no one obtains in the first 50% or another qualified majority. The double round was first established in 1949 and since 1979 has spread across the continent. Only five Spanish-speaking countries, plus the United States, hold the majority-runoff. We already have enough evidences and data to analyze whether the double turn has benefited democracy and institutions of countries that have incorporated it into their Constitutions.
Keywords: Second round; presidential system; electoral college; ballotage